Loss of the neural-specific BAF subunit ACTL6B relieves repression of early response genes and causes recessive autism. - Wenderski, Wendy; Wang, Lu; Krokhotin, Andrey; Walsh, Jessica J; Li, Hongjie; Shoji, Hirotaka; Ghosh, Shereen; George, Renee D; Miller, Erik L; Elias, Laura; Gillespie, Mark A; Son, Esther Y; et al. (Proc Natl Acad Sci U S A, 2020)
Synaptic activity in neurons leads to the rapid activation of genes involved in mammalian behavior. ATP-dependent chromatin remodelers such as the BAF complex contribute to these responses and are generally thought to activate transcription. However, the mechanisms keeping such "early activation" genes silent have been a mystery. In the course of investigating Mendelian recessive autism, we identified six families with segregating loss-of-function mutations in the neuronal BAF (nBAF) subunit (originally named ). Accordingly, was the most significantly mutated gene in the Simons Recessive Autism Cohort. At least 14 subunits of the nBAF complex are mutated in autism, collectively making it a major contributor to autism spectrum disorder (ASD). Patient mutations destabilized ACTL6B protein in neurons and rerouted dendrites to the wrong glomerulus in the fly olfactory system. Humans and mice lacking showed corpus callosum hypoplasia, indicating a conserved role for in facilitating neural connectivity. knockout mice on two genetic backgrounds exhibited ASD-related behaviors, including social and memory impairments, repetitive behaviors, and hyperactivity. Surprisingly, mutation of relieved repression of early response genes including AP1 transcription factors (, , , and ), increased chromatin accessibility at AP1 binding sites, and transcriptional changes in late response genes associated with early response transcription factor activity. loss is thus an important cause of recessive ASD, with impaired neuron-specific chromatin repression indicated as a potential mechanism.
Keywords: Actins; Adenosine Triphosphate; Animals; Autism Spectrum Disorder; Behavior, Animal; Chromatin; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; Chromosome Pairing; Corpus Callosum; Dendrites; Disease Models, Animal; DNA-Binding Proteins; Gene Expression Regulation; Hippocampus; Humans; Mice; Mice, Knockout; Mutation; Neurons; Transcription Factors

Recessive Inactivating Mutations in TBCK, Encoding a Rab GTPase-Activating Protein, Cause Severe Infantile Syndromic Encephalopathy. - Chong, Jessica X; Caputo, Viviana; Phelps, Ian G; Stella, Lorenzo; Worgan, Lisa; Dempsey, Jennifer C; Nguyen, Alina; Leuzzi, Vincenzo; Webster, Richard; Pizzuti, Antonio; Marvin, Colby T; Ishak, Gisele E; et al. (Am J Hum Genet, 2016)
Infantile encephalopathies are a group of clinically and biologically heterogeneous disorders for which the genetic basis remains largely unknown. Here, we report a syndromic neonatal encephalopathy characterized by profound developmental disability, severe hypotonia, seizures, diminished respiratory drive requiring mechanical ventilation, brain atrophy, dysgenesis of the corpus callosum, cerebellar vermis hypoplasia, and facial dysmorphism. Biallelic inactivating mutations in TBCK (TBC1-domain-containing kinase) were independently identified by whole-exome sequencing as the cause of this condition in four unrelated families. Matching these families was facilitated by the sharing of phenotypic profiles and WES data in a recently released web-based tool (Geno2MP) that links phenotypic information to rare variants in families with Mendelian traits. TBCK is a putative GTPase-activating protein (GAP) for small GTPases of the Rab family and has been shown to control cell growth and proliferation, actin-cytoskeleton dynamics, and mTOR signaling. Two of the three mutations (c.376C>T [p.Arg126(∗)] and c.1363A>T [p.Lys455(∗)]) are predicted to truncate the protein, and loss of the major TBCK isoform was confirmed in primary fibroblasts from one affected individual. The third mutation, c.1532G>A (p.Arg511His), alters a conserved residue within the TBC1 domain. Structural analysis implicated Arg511 as a required residue for Rab-GAP function, and in silico homology modeling predicted impaired GAP function in the corresponding mutant. These results suggest that loss of Rab-GAP activity is the underlying mechanism of disease. In contrast to other disorders caused by dysregulated mTOR signaling associated with focal or global brain overgrowth, impaired TBCK function results in progressive loss of brain volume.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Brain Diseases; Child; Child, Preschool; Corpus Callosum; Female; GTPase-Activating Proteins; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Protein-Serine-Threonine Kinases; Signal Transduction; TOR Serine-Threonine Kinases